Comorbilidades en pacientes con infección por Covid-19 grave posvacunación en el Hospital Juárez de México - Cesar Daniel Alonso-Bello; Evelyn Aranda-Cano; Jhizzel Otero-Leyva; Edwin Mondragón-Jiménez; Dennis Marcel Callao-Torrico; Heber Gabriel Manzano-Martínez; Carlos Chico-Juárez; Lizbeth Teresa Becerril-Mendoza; Carol Vivian Moncayo-Coello; María Isabel Rojo-Gutiérrez (Instituto Nacional de Salud Pública, 2023)
No disponible